Proximal Femural Fracture: Perioperative Approach to the Patient doing Anticoagulation and Antiplatelet Agents Based on the Recommendations of the Portuguese Society of Anesthesiology 2014, with the support of the Portuguese Imunohemotherapy Association a - Fonseca, Cristiana; Marta, Miguel; Dias, José; Pinto, Rui; Bettencourt, Paulo; Maciel, Júlia; Araújo, Fernando (Journal of the Portuguese Society of Anesthesiology, 2015)
The proximal femoral fracture, which usually occurs in the elderly, is a commoncause of morbidity and mortality in this age group. These patients have severalco-morbidities and are often poly-medicated, factors contributing to a prolongedhospitalization, increased perioperative complications and mortality. Evidence suggeststhat early surgery reduces the morbidity and mortality associated withproximal femur fracture, while postponement beyond 48 hours is associatedwith higher postoperative mortality and complications at 30 days of hospitalization.The perioperative management of these patients is complex. Surgical delay usuallyoccurs in the presence of anticoagulants and antiplatelet drugs. In order to normalize the peri-operative procedures in these patients, it has been created amultidisciplinary working group that had as main objective the application of therecommendations of the Portuguese Society of Anesthesiology on the perioperativemanagement of patients treated with anticoagulants, published in 2014.A multidisciplinary analysis of literature based on the peri-operative treatment ofpatients proposed for surgical treatment of femoral neck fracture was performed.Several issues are subject of interest and analysis, such as reversal of anticoagulantdrugs, patient blood management and thromboprophylaxis and it was developed anactuation protocol. The establishment of multidisciplinary algorithms for the perioperativeapproach of patients with femoral neck fracture is essential to facilitate thedaily clinical practice.